Cardiac safety of trabectedin monotherapy or in combination with pegylated liposomal doxorubicin in patients with sarcomas and ovarian cancer. (7th May 2021) - Jones, Robin L.; Herzog, Thomas J.; Patel, Shreyaskumar R.; von Mehren, Margaret; Schuetze, Scott M.; Van Tine, Brian A.; Coleman, Robert L.; Knoblauch, Roland; Triantos, Spyros; Hu, Peter; Shalaby, Waleed; McGowan, Tracy; et al.
Abstract: Background: As with other alkylating agents, cardiac dysfunction can occur with trabectedin therapy for advanced soft tissue sarcomas (STS) or recurrent ovarian cancer (ROC) where treatment options for advanced disease are still limited. Cardiac safety for trabectedin monotherapy (T) for STS or in combination with pegylated liposomal doxorubicin (T+PLD) for ROC was evaluated in this retrospective postmarketing regulatory commitment. Methods: Patient data for multiple cardiac‐related treatment‐emergent adverse events (cTEAEs) were evaluated in pooled analyses of ten phase 2 trials, one phase 3 trial in STS ( n = 982), and two phase 3 trials in ROC ( n = 1231). Results: Multivariate analyses on pooled trabectedin data revealed that cardiovascular medical history (risk ratio [RR (95% CI)]: 1.90 [1.24‐2.91]; p = 0.003) and age ≥65 years (RR [95% CI]: 1.78 [1.12‐2.83]; p = 0.014) were associated with increased risk for cTEAEs. Multivariate analyses showed increased risk of experiencing cTEAEs with T+PLD compared to PLD monotherapy (RR [95% CI]: 2.70 [1.75‐4.17]; p < 0.0001) and with history of prior cardiac medication (RR [95% CI]: 1.88 [1.16‐3.05]; p = 0.010). Conclusions: For patients with STS or ROC who still have limited treatment options, trabectedin may be initiated after carefully considering benefit versus risk. Trial Registration (ClinicalTrials.gov): NCT01343277; NCT00113607; NCT01846611. Abstract : Cardiac safety for trabectedin monotherapy advanced soft tissue sarcomas (STS) or in combination with pegylated liposomal doxorubicin (T+PLD) for recurrent ovarian cancer (ROC) was evaluated in pooled analyses of 10 phase 2 trials, one phase 3 trial in STS ( n = 982), and two phase 3 trials in ROC ( n = 1231). Cardiovascular medical history, age ≥65 years, and prior use of anthracyclines were associated with increased risk for cTEAEs. For patients with STS or ROC who still have limited treatment options, trabectedin may be initiated after carefully considering benefit versus risk.